2006
DOI: 10.1159/000091412
|View full text |Cite
|
Sign up to set email alerts
|

Otolith Function Assessed with the Subjective Postural Horizontal and Standardised Stance and Gait Tasks

Abstract: If otolith function is essential to maintain upright standing while moving along slanted or uneven surfaces, subjects with an otolith deficit should have difficulty judging whether the inclination of the surface on which they are standing is tilted or not. We tested this judgement and compared it with the ability to control trunk sway during standardised stance and gait tests. Thirteen patients with unilateral vestibular nerve neurectomy at least 6 months prior to testing and 39 age-matched controls were asked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 78 publications
3
18
0
Order By: Relevance
“…Second, the neurectomy patients had complete otolith lesions. Similar results for stance and gait tasks were obtained by Beule and Allum [2006] for cerebellar pontine angle tumor patients after VN following tumor removal. Furthermore, Beule and Allum [2006] were also able to show that the ability to judge offsets from the true horizontal were impaired in their patient population, indicating a deficit in otolith responses.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Second, the neurectomy patients had complete otolith lesions. Similar results for stance and gait tasks were obtained by Beule and Allum [2006] for cerebellar pontine angle tumor patients after VN following tumor removal. Furthermore, Beule and Allum [2006] were also able to show that the ability to judge offsets from the true horizontal were impaired in their patient population, indicating a deficit in otolith responses.…”
Section: Discussionsupporting
confidence: 81%
“…In the event, we had very significant results for 14 subjects with low AAO-HNS scores. An alternative estimate of sample size would have been to take the number of patients used in a study of a similar population, those with a neurectomy due to removal of a cerebellar pontine angle tumor [Beule and Allum, 2006]. Beule and Allum [2006] showed similar results as our current study with 14 patients.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Beule and Allum [20] previously described a test of PPV whereby participants standing on a movable support platform were required to return the platform to the horizontal position following tilts in roll and pitch planes using a joystick. The authors found that patients with unilateral otolith disorders performed worse than healthy age-matched controls on this task, and suggested that this test could be used as a simple clinical test of otolith function.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent research demonstrates the important role played by the somatosensory system to update humans’ internal models of verticality [18,19], in the absence of lower limb somatosensory and visual input, PPV is likely primarily modulated by the vestibular system [20]. In fact, Beule and Allum [20] reported that compared with healthy controls, patients with unilateral loss of otolith input showed significantly greater deviations from the vertical when asked to move the support platform on which they stood back to the vertical following forward left and right tilts as well as tilts in the roll plane. In addition, previous research has shown that while young healthy adults can report PPV accurately within a tight ‘angle of uncertainty’ [21], older people have greater difficulty re-aligning themselves vertically after being tilted [22,23].…”
Section: Introductionmentioning
confidence: 99%